Persistent bothersome urinary frequency following stereotactic body radiation therapy for clinically localized prostate cancer: rationale for prophylactic β3-agonist in men with elevated baseline international prostate symptom scores - Zack, Jennifer; Koh, Min Ji; Lindbloom, Emily; O’Connor, Timothy; Gaudian, Kelly; Zwart, Alan; Danner, Malika; Kumar, Deepak; Suy, Simeng; Hankins, Ryan; Collins, Sean (Frontiers in Oncology, 2026)
IntroductionStereotactic body radiation therapy (SBRT) for clinically localized prostate cancer has been associated with prolonged acute obstructive and irritative lower urinary tract symptoms (LUTS). Prophylactic alpha-adrenergic antagonists have been used therapeutically to prevent obstructive symptoms in patients undergoing prostate SBRT, however irritative symptoms may be better addressed with beta 3-adrenergic receptor agonists, which are shown to be safe and effective in men with overactive bladder (OAB).ObjectiveThis study retrospectively examines the pattern of bothersome urinary frequency associated with SBRT to determine which patients would have potentially benefitted from prophylactic beta 3-adrenergic receptor agonist.MethodsPatients with clinically localized prostate cancer who underwent prostate SBRT (n=1676) were followed for 3 months post-treatment to evaluate for bothersome urinary frequency, which was assessed by question 4E on the EPIC-26. Answers to question 4E and tamsulosin usage were recorded at regular follow-ups to assess, and demographic factors as well as baseline prostate volume, alpha-adrenergic antagonist usage and IPSS score severity were used as modifiers.ResultsUsing the IPSS questionnaire to determine baseline LUTS, most patients reported moderate urinary symptoms (53%), followed by mild (34%) and severe (13%). Patients endorsed increased irritative LUTS at 1-month post-SBRT, with similar rates of frequency at 3 months compared to baseline. Patients with moderate and severe urinary symptoms per the baseline IPSS were more likely to endorse bothersome urinary frequency at one month post SBRT (EPIC-26 Q4E; OR 2.58 and 10.2 respectively) compared to those with mild symptoms. No significant differences were found in urinary frequency between patients who used and did not use an alpha antagonist at baseline.ConclusionsBothersome post-SBRT urinary frequency persists 1-month post-SBRT. Baseline LUTS predicts bothersome post-treatment urinary frequency. Prophylactic alpha-adrenergic antagonists do not protect against bothersome acute urinary frequency. This paper makes the case that urinary frequency may be better addressed with a prophylactic beta-3 agonist, like vibegron, which is designed to treat storage-related LUTS concerns.